Safety, Clinical Response, and Microbiome Findings Following Fecal Microbiota Transplant in Children With Inflammatory Bowel Disease. Issue 2 (18th January 2018) - Goyal, Alka; Yeh, Andrew; Bush, Brian R; Firek, Brian A; Siebold, Leah M; Rogers, Matthew Brian; Kufen, Adam D; Morowitz, Michael J
Abstract: Background: The role of fecal microbiota transplant (FMT) in the treatment of pediatric inflammatory bowel disease (IBD) is unknown. The aims of this study were to assess safety, clinical response, and gut microbiome alterations in children with Crohn's disease (CD), ulcerative colitis (UC), or indeterminate colitis (IC). Methods: In this open-label, single-center prospective trial, patients with IBD refractory to medical therapy underwent a single FMT by upper and lower endoscopy. Adverse events, clinical response, gut microbiome, and biomarkers were assessed at baseline, 1 week, 1 month, and 6 months following FMT. Results: Twenty-one subjects were analyzed, with a median age of 12 years, of whom 57% and 28% demonstrated clinical response at 1 and 6 months post-FMT, respectively. Two CD patients were in remission at 6 months. Adverse events attributable to FMT were mild to moderate and self-limited. Patients prior to FMT showed decreased species diversity and significant microbiome compositional differences characterized by increased Enterobacteriaceae, Enterococcus, Haemophilus, and Fusobacterium compared with donors and demonstrated increased species diversity at 30 days post-FMT. At 6 months, these changes shifted toward baseline. Clinical responders had a higher relative abundance of Fusobacterium and a lower diversity at baseline, as well as a greater shift toward donor-like microbiome after FMT compared with nonresponders. Conclusions: A single FMT is relatively safe and can result in a short-term response in young patients with active IBD. Responders possessed increased Fusobacterium prior to FMT and demonstrated more significant microbiome changes compared with nonresponders after FMT. Microbiome characteristics may help in predicting response.